How Does the Periodic Groundwater Table Fluctuation Impact on Chlorinated Vapor Intrusion? - Honghong Zhang; Yu Ye; Xin Yang (Geofluids)
Periodic groundwater table fluctuations are found frequently in natural aquifers due to sea tides or seasonal recharge. However, their impact on the transport of volatile organic compounds in the vadose zone released from a groundwater contaminant source (i.e., vapor intrusion) has not been well known. A 2D numerical model was developed to explore vapor intrusion processes in the sandy vadose zone, subject to a fluctuating groundwater table with a range of fluctuation amplitudes and periods. A carcinogenic compound, Trichloroethylene (TCE), was chosen as the groundwater contaminant of interest in the current study and assumed to transport into the dwelling through a crack at the corner of the basement. Results showed that the resistant effect caused by high soil moisture contents in the thin capillary fringe is weakened by periodic groundwater table fluctuations, resulting in a higher concentration of gaseous TCE at the building foundation crack, in comparison with that under a static groundwater table. The increase of the gaseous TCE concentration was induced by the enhancement of diffusion and advection due to groundwater table fluctuations. Sensitivity analyses indicated that a higher amplitude and frequency of fluctuations lead to a higher TCE concentration at the crack under the dynamic equilibrium condition. Specifically, compared with the static groundwater table condition, the TCE concentration at the crack increased by one order of magnitude under the condition of groundwater table fluctuations with an amplitude of 0.2 m and a period of one day. The results obtained could provide insights into the importance of the amplitude and frequency of groundwater table fluctuations on vapor intrusion.